KEBIJAKAN HUKUM PIDANA NON – PENAL DALAM MENANGGULANGI PERBUATAN PIDANA PEMALSUAN SURAT BEBAS CORONA VIRUS DISEASE 2019 - Teerza Febe Jennifer (Jurnal Hukum Adigama, 2021)
The current Covid-19 in Indonesia has made the Government set several new policies in order to prevent the spread of the coronavirus. One of them is to show a rapid test when going to work or vacation. But, at this time too many people took the opportunity to take a fake rapid test. Even Though the rapid test should not be faked when conditions are not conductive like this because it can harm yourself and other people. This matter must be resolved as soon as possible both penal and non-penal. This research will be a normative legal research with statutory law and factual law. Through of this journal, will explained the concept of non-penal in tackling the criminal act of letter forgery. Actually, forgery letter has been regulated in the criminal law code, article 263 to 276. However, the increasing number of forgery letter cases proves that the penal policy is nit enough, so it needs to be accompanied by a non-penal policy.